Aspetos da gramaticalização de ’ir’ como verbo auxiliar temporal - Móia, Telmo (Revista da Associação Portuguesa de Linguística, 2020)
In this paper, various aspects concerning the grammaticalization of ir (‘go’) into a temporal auxiliary verb are considered, focusing on its current status as a posteriority operator in competition with various temporal suffixes of the tense system. Four issues will hold center stage: its coexistence with explicit posteriority tense suffixes, without a sense of redundancy emerging; its use in non-past and past scenarios in competition with the synthetic future and with the synthetic conditional, or imperfective past, respectively; its possible use in structures expressing an anteriority location relation (in association with future perspective points); its inflection in subjunctive, gerundive and infinitival forms, a rather poorly studied possibility. The overall conclusion will be that the grammaticalization process affecting ir is still an ongoing process, which can be seen not only in the aspects studied apropos the abovementioned four issues, but also in a few other aspects – namely regarding the scarcity of its combination with some classes of predicates – that will be left for further research.